Follow-up after gastrectomy for cancer: the Charter Scaligero Consensus Conference - Baiocchi, Gian Luca; Ott, Katja (Gastric cancer, 2016)
Presently, there is no scientific evidence supporting a definite role for follow-up after gastrectomy for cancer, and clinical practices are quite different around the globe. The aim of this consensus conference was to present an ideal prototype of follow-up after gastrectomy for cancer, based on shared experiences and taking into account the need to rationalize the diagnostic course without losing the possibility of detecting local recurrence at a potentially curable stage.
Published: 04 July 2015
Gesehen am 29.07.2020